2007
DOI: 10.1159/000104407
|View full text |Cite
|
Sign up to set email alerts
|

Extraneural Arterial Blood Vessels of Human Fetal Sciatic Nerve

Abstract: Nerves get segmental blood supply either from the neighboring muscular and cutaneous branches or from the regional main arterial trunks. The aim of our research was to detect, in the gluteal and posterior femoral region, the blood vessels which are involved in the blood supply of the human fetal sciatic nerve, as well as to establish their origin. Micro-dissection was performed on 48 fetal lower extremities which were previously fixed in 10% formalin. Micropaque solution (barium sulfate) was injected into thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Georgakis and Soames () observed the accompanying artery of the sciatic nerve to be a branch of the medial circumflex femoral artery in 50%, inferior gluteal artery in 39%, the first perforating artery in 7%, and internal pudendal artery in 4% of specimens. In the present as well as our previous research (Ugrenovic et al, ), we observed it solely as a branch of the inferior gluteal artery. The number of popliteal artery branches supplying the sciatic nerve differed between this and our previous research (Ugrenovic et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Georgakis and Soames () observed the accompanying artery of the sciatic nerve to be a branch of the medial circumflex femoral artery in 50%, inferior gluteal artery in 39%, the first perforating artery in 7%, and internal pudendal artery in 4% of specimens. In the present as well as our previous research (Ugrenovic et al, ), we observed it solely as a branch of the inferior gluteal artery. The number of popliteal artery branches supplying the sciatic nerve differed between this and our previous research (Ugrenovic et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…In the present as well as our previous research (Ugrenovic et al, ), we observed it solely as a branch of the inferior gluteal artery. The number of popliteal artery branches supplying the sciatic nerve differed between this and our previous research (Ugrenovic et al, ). In this study, the popliteal artery gave off the branch for the sciatic nerve supply in 19.4% of the specimens, higher than 8.3% of the dissections observed during our earlier research.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Does the foetal sciatic nerve have an accompanying space that would favour secondary development of a longitudinal artery? The sciatic nerve receives multiple feeding arteries, especially from the deep femoral artery, in foetuses [38] as well as in adults [10,16]. Consequently, the primary aim of this study was to determine the human foetal topographical anatomy of the sciatic nerve around the highly flexed hip joint.…”
Section: Introductionmentioning
confidence: 99%